KERENTANAN DAN STRATEGI NAFKAH RUMAH TANGGA PETANI DI KAMPUNG KALISEMEN DISTRIK NABIRE BARAT KABUPATEN NABIRE - Hans F Liborang (Jurnal FAPERTANAK : Jurnal Pertanian dan Peternakan, 2020)
This study research to determine how the livelihood strategies of farmer households and vulnerabilities in Kalisemen village, West Nabire District, Nabire Regency. This research approach used a qualitative approach, and the research location was conducted in Kalisemen Village, West Nabire District, Nabire Regency, which was conducted from March to May The data used in this research were primary data and secondary data. Data collection techniques used interview methods, observation, and document analysis (triangulation principle). Qualitative data analysis is carried out continuously which consists of data collection, data analysis, data reduction, where the data is processed by carrying out three stages of activities and carried out simultaneously, namely data reduction, data presentation and drawing conclusions through data verification. The results of this research indicate that farmers' livelihoods in the agricultural sector (on farm) are vulnerable because arable land is not functioning. To solve this problem, farmers use 2 strategies, namely the survival strategy by selling livestock and borrowing money from neighbors or relatives. Some farmers employ a spatial strategy (migration) to the city center of Nabire as workmen in workshops, construction workers or as masons, but it is not permanent.